Improving the Sustainability of MSMES Businesses Through Digital Business Development in Tegal Parang Urban Village, Mampang Prapatan Sub-District, South Jakarta - Dinar Nur AFFINI; Aldina SHIRATINA; Retno Purwani SETYANINGRUM (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Business development in Indonesia is happening fast and has given birth to many examples of digital businesses with diverse business models. This requires every business owner to be able to adapt and find new opportunities for business growth. This digital business model also aligns with the government program that targets 30 million MSME businesses to go digital by 2024. MSME players must keep up with technological developments to spread to a broader market, so they must try to familiarize MSME players with digital behavior. This activity is a Community Service Programme (PkM) that aims to improve the sustainability of MSME businesses through digital business development training for MSME participants. This activity is expected to provide meaningful benefits for the participants, where the participants, after attending the training, can better understand the importance of digitalization in the businesses they run. Also, the participants are expected to be able to be more effective and efficient in running their businesses using digital technology. The final result to be obtained is that MSMEs can maintain the sustainability of their business by being able to compete in the global market, have high innovation, and be strong in facing future challenges.